Environmental Education and values in the practice of a teacher: meanings produced - Bianchini Bonotto, Dalva Maria [UNESP] (Univ Metodista Piracicaba-unimep, 2015)
As we recognize the need to change the hegemonic value system that supports the current standard of unsustainable relationship between society and nature, we are interested in investigate the possibilities of strengthening up counter-hegemonic ideologies. Educational programs should contribute to this task, bringing students closer to thoughts, positions and values of social and environmental interest, so that the proposals and these values can be of significance to them. So we propose to investigate the construction of meaning by teachers interested in environmental education. In this paper we aim to present some meanings produced by a primary school teacher while she seeked to incorporate in her classes the work with the values dimension of environmental issues. This teacher's practice seemed impregnated with the sense of challenge, as she was faced with the task of expanding the mindset of her students - children - about an environmental problem in a more critical way, in accordance with the understandings she herself had elaborated in the in-service teacher program that she participated. This meaning was permeated with her optimistic willingness to cooperate with the facing of the environmental crisis and the environmental and social transformation with which we aim.
Keywords: ENVIRONMENTAL EDUCATION AND VALUES; MEANINGS; PRIMARY SCHOOL